Accessibility Analysis of Basic Infrastructure in Pal IX Village, Sungai Kakap Sub-District, Kubu Raya Regency - Aulia, Nurul Rahmi; Azwansyah, Heri; Mukti, Elsa Tri (Jurnal Teknik Sipil, 2025)
In rural areas, infrastructure is crucial for supporting social and economic development. It encompasses technical facilities, physical systems, hardware, and software needed to provide services to the community and support structural networks, ensuring the smooth progress of economic and social growth. This study aims to analyze the accessibility of basic infrastructure and determine the road priority ranking in Pal IX Village, Sungai Kakap Subdistrict, Kubu Raya Regency, using the Integrated Rural Accessibility Planning (IRAP) method and Geographic Information Systems (GIS). The analysis results using the IRAP method indicate that the highest priority sector in Pal IX Village is Primary School Education (SMP), with an accessibility value of 10,52. Meanwhile, the road benefit analysis, using IRAP and GIS, shows that the highest priority road is Jalan Kalimas Hulu, with a road benefit accessibility value of 18,12. The IRAP method is effective for planning and improving rural accessibility by utilizing GIS for data analysis and mapping. GIS allows for more accurate and efficient data collection, processing, and visualization related to infrastructure and accessibility. Using software like ArcGIS 10.8, this study provides a map that identifies priorities and real conditions based on field data.